Black Holes and Neutron Stars in Galactic Globular Clusters - Paduano, Alessandro (Curtin University, 2023)
In this thesis I observed black holes and neutron stars in Galactic globular clusters with radio and X-ray telescopes to explore the unique properties of these systems. I investigated the extreme and unusual accretion scenarios that are found in these systems. Finally, I created the most sensitive radio image made using an Australian radio telescope to detect the very faintly accreting black holes in globular clusters in preparation for science with the Square Kilometre Array.